2007
DOI: 10.1074/jbc.m608867200
|View full text |Cite
|
Sign up to set email alerts
|

TAK1-dependent Signaling Requires Functional Interaction with TAB2/TAB3

Abstract: Transforming growth factor ␤-activated kinase 1 (TAK1), a member of the MAPKKK family, was initially described to play an essential role in the transforming growth factor ␤-signaling pathway, but recent evidence has emerged implicating TAK1 in the interleukin (IL)-1 and tumor necrosis factor (TNF) pathways. Notably, two homologous proteins, TAB2 and TAB3, have been identified as adaptors linking TAK1 to the upstream adaptors TRAFs. However, it remains unclear whether the interaction between TAB2/TAB3 and TAK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 49 publications
3
117
0
Order By: Relevance
“…The WNT4 gene is the member of the Wnt ligands and has been identified as being associated with the vertebral cross-sectional area (CSA) in older Caucasian men, (22) whereas TAB2 may regulate osteoblastogenesis and the development and function of osteoclasts. (23,24) Note that the candidate gene variants for osteoporotic fracture are not simply the same as those for low BMD. (8,25) In addition to BMD, the bone matrix, bone strength, falling risk, and environmental factors take responsibility for osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The WNT4 gene is the member of the Wnt ligands and has been identified as being associated with the vertebral cross-sectional area (CSA) in older Caucasian men, (22) whereas TAB2 may regulate osteoblastogenesis and the development and function of osteoclasts. (23,24) Note that the candidate gene variants for osteoporotic fracture are not simply the same as those for low BMD. (8,25) In addition to BMD, the bone matrix, bone strength, falling risk, and environmental factors take responsibility for osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation and activation of TAK1 subsequently leads to MAPKs and inhibitory κB kinase (IKK) activation, the prerequisite event necessary to induce NF-κB. In this process, TAK1-associated binding protein-2 (TAB2) acts as a bridge linking TRAF6 to TAK1 [26]. Although the mechanism by which TAK1 is activated is not fully understood, many studies have revealed the critical role of the lysine-63-linked polyubiquitination by TRAF6 in the activation of TAK1 [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The TAB2 NZF domain has been shown to interact with K63-type, but not linear, polyubiquitin chains (15)(16)(17). TAB2 and TAB3 interact with K63-linked polyubiquitin chains and activate TAK1-mediated NF-kB activation (18,19). NEMO also has the potential to bind K63-linked polyubiquitin chains, but the affinity of NEMO for linear polyubiquitin chains seems to be even greater than for K63-linked ubiquitin chains (20,21).…”
mentioning
confidence: 99%